Adult strabismus and social phobia: A case-controlled study - TOPÇUOĞLU, VOLKAN (MOSBY-ELSEVIER, 2009)
PURPOSE To determine the social phobia rate, social anxiety level, severity of depressive symptoms, and disease-related disability in adult strabismus patients. METHODS Forty-nine strabismus patients and 46 control subjects from 15 to 65 years of age were evaluated. A psychiatric interview focusing on social phobia and the Liebowitz Social Anxiety Scale (LSAS) were administered to each participant. All participants completed the Hospital Anxiety and Depression Scale (HADS), a psychiatric symptom checklist (Symptom Checklist 90-Revised; SCL-90R), and the Sheehan Disability Scale. RESULTS Social phobia was diagnosed in 26 of the 49 strabismus patients and in 8 of the 46 control subjects (p < 0.001). Strabismus patients demonstrated significantly greater scores in all of the subscores and the total scores of LSAS. They were more disabled in social life, family life, and at work. They also showed greater interpersonal sensitivity scores compared with the control group. Compared with strabismus patients without social phobia, the strabismus patients with social phobia demonstrated significantly greater depression scores in HADS and also scored in all dimensions of LSAS. Their social life and family life scores in disability scale and all scores in SCL-90-R except somatization were better than strabismus patients without social phobia. CONCLUSIONS In adult strabismus patients, social phobia is a frequent psychiatric comorbidity. Adult patients with strabismus need to be carefully evaluated for social phobia for an appropriate referral and treatment. (J AAPOS 2009;13:249-252)
Keywords: QUALITY-OF-LIFE; PSYCHOSOCIAL-ASPECTS; ESSENTIAL TREMOR; IMPACT; SURGERY; DISABILITY; MANAGEMENT